Nondestructive testing method based on maltodextrin tablets

Through the non-destructive detection method based on maltodextrin tablets, the phosphorescence life and afterglow image analysis technology is used to solve the problem of the existing tablet detection methods damaging the environment, and the detection effect is achieved without loss, green and environmentally friendly.

CN119394994AActive Publication Date: 2025-02-07JIANGXI UNIVERSITY OF TRADITIONAL CHINESE MEDICINE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510013075.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-02-07
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing tablet quality testing methods will cause damage to the tablets, produce medicinal waste, lead to environmental pollution and reduced utilization, and lack of non-destructive testing methods.

Method used

The non-destructive detection method based on maltodextrin tablets was used to measure the phosphorescence life by a transient/steady state fluorescence spectrometer, and combined with the afterglow image analysis after ultraviolet lamp irradiation, the hardness, humidity, disintegration time limit and content uniformity of the tablets were evaluated. .

Benefits of technology

The hardness, humidity, disintegration time limit and content uniformity of the tablet are achieved by non-destructive testing, and it determines whether the tablet is damp and deteriorated. It has the characteristics of green, environmentally friendly, safe, and no medicinal waste generation, and has wide application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119394994A_ABST
    Figure CN119394994A_ABST
Patent Text Reader

Abstract

The invention discloses a nondestructive testing method based on a maltodextrin tablet, and relates to the technical field of nondestructive testing of tablets, the nondestructive testing method based on the maltodextrin tablet comprises the following steps: S1, preparing tablets: preparing a plurality of maltodextrin-containing tablets with different hardness; s2, testing the phosphorescence lifetime of the maltodextrin-containing tablet: fitting the phosphorescence lifetime according to a multi-exponential function by using transient / steady-state fluorescence spectrophotometer matched software under the excitation wavelength of 254 nm through a transient / steady-state fluorescence spectrophotometer, and calculating the average phosphorescence lifetime tau avg according to the phosphorescence lifetime; s3, detecting an afterglow image of the tablet containing maltodextrin; s4, evaluating the performance index of the tablet according to the phosphorescence lifetime and afterglow image of the tablet; according to the nondestructive testing method based on the maltodextrin tablet provided by the invention, the characteristics of hardness, humidity, disintegration time limit and content uniformity of the tablet can be subjected to nondestructive testing; the method is green, environment-friendly, safe and free of medicinal waste, and has economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technology of tablet nondestructive testing, in particular to a nondestructive testing method based on maltodextrin tablets. Background Art

[0002] Tablet quality inspection is a key step in tablet production and is closely related to human health. It has received extensive attention in recent years. The existing tablet quality inspection methods mainly use instruments to detect various indicators such as tablet hardness, water content, disintegration time, content uniformity, etc. These methods will damage the tablets, generate a large amount of pharmaceutical waste, and cause environmental pollution. Large-scale destructive testing leads to reduced tablet utilization and reduced economic efficiency. Non-destructive testing, as a new type of testing method, has received extensive attention in recent years due to its rapidity, safety, and environmental protection. Room temperature phosphorescent materials are materials that respond to stimuli such as pressure, humidity, temperature, gas, and pH. They are often used in light-emitting diode displays, biomedical imaging, rapid detection, anti-counterfeiting, and encryption. After being irradiated by ultraviolet light, room temperature phosphorescent materials have afterglow effects of different intensities. Compared with fluorescent images, the afterglow images of room temperature phosphorescent materials have a larger signal-to-noise ratio during the detection process, which can not only eliminate the interference of scattered light and background fluorescence, but also provide rich information according to different response stimuli.

[0003] In recent years, non-aromatic polymers with luminescent properties have attracted widespread attention due to their advantages such as easy availability, renewability and processing, convenient structural modification, and strong biocompatibility. In the pharmaceutical field, most excipients are derived from non-aromatic polymers. These polymers contain more hydroxyl groups and form strong hydrogen bonds within the molecules, which is conducive to the generation of phosphorescence. Maltodextrin (MD), as a polysaccharide food raw material with a multi-hydroxy structure, can be observed to have an obvious afterglow phenomenon after being irradiated by ultraviolet light, and is a room temperature phosphorescent material. Due to its stable physicochemical properties, difficulty in absorbing moisture, and difficulty in deterioration, it is usually used as a filler in tablets. At present, the quality inspection method of tablets has become mature, but there is still a gap in the non-destructive inspection of tablet quality. We urgently need to find a non-destructive inspection method based on maltodextrin tablets. Summary of the invention

[0004] In view of this, the present invention aims at the deficiencies in the prior art, and its main purpose is to provide a nondestructive testing method based on maltodextrin tablets, which can nondestructively test the characteristics of tablet hardness, humidity, disintegration time, and content uniformity; the nondestructive testing method provided by the present invention can determine whether the tablets are damp and deteriorated during transportation and storage, and has wide application value; the nondestructive testing method provided by the present invention is green, environmentally friendly, safe, does not generate any medicinal waste, and has economic value.

[0005] To achieve the above purpose, the present invention adopts the following technical solutions: A nondestructive testing method based on maltodextrin tablets comprises the following steps: S1. Preparing tablets: preparing a plurality of tablets containing maltodextrin of different hardness, wherein the hardness of each tablet is uniform; S2. Test the phosphorescence lifetime of maltodextrin tablets: Use a transient / steady-state fluorescence spectrometer equipped with a xenon lamp and a microsecond flash lamp to fit the phosphorescence lifetime according to a multi-exponential function using the transient / steady-state fluorescence spectrometer software at an excitation wavelength of 240-260nm, and calculate the average phosphorescence lifetime τ based on the phosphorescence lifetime avg ; Phosphorescence lifetime is the decay curve of the monitored emission wavelength under light source excitation; S3. Detecting the afterglow image of the tablet containing maltodextrin: The afterglow image of the tablet is obtained by shooting. A 240-260 nm fixture UV lamp is fixed to the side of the tablet. After irradiation with the UV lamp for 5-15 seconds, the afterglow image is recorded. The afterglow image is analyzed frame by frame by video analysis software to capture the afterglow image of the tablet. The average gray value of the image is analyzed by "ImageJ" software to quantify the afterglow image. S4. Evaluate the performance indicators of the tablets based on the phosphorescence lifetime and afterglow image of the tablets.

[0006] As a preferred solution: the multi-exponential function used in fitting the phosphorescence lifetime in step S2 is: , and by the formula Calculate the average phosphorescence lifetime τ avg ; Where: R(t) represents the phosphorescence lifetime, t represents time, τ i Represents different types of phosphorescence lifetimes, including radiative transition lifetime τ1, non-radiative transition lifetime τ2, and other forms of lifetime τ3. Bi represents the percentage of different types of phosphorescence lifetimes.

[0007] As a preferred solution: the excitation wavelength in step S2 is 254 nm; in step S3, a 254 nm fixture UV lamp is fixed at a distance of 5 cm from the tablet surface, and after irradiation with the UV lamp for 10 seconds, an afterglow image is recorded for 5 seconds.

[0008] As a preferred solution: the performance index of the tablets evaluated in step S4 includes humidity detection and evaluation of the tablets: maltodextrin tablets with a hardness of 100N are selected for a hygroscopicity experiment, the biochemical incubator is set at 25°C, the tablets are placed in a dryer with saturated salt, four saturated salt solutions of LiCl, K2CO3, KI, and K2SO4 are prepared, and the relative humidity is set to 11%, 43%, 69%, and 94% respectively for storage; after 6 hours, the tablets are taken out and the phosphorescence lifetime and afterglow image are detected to evaluate their humidity conditions.

[0009] As a preferred solution: the performance indicators of the tablets evaluated in step S4 include the disintegration time detection and evaluation of the tablets: the method for determining the disintegration time is the hanging basket method, taking the tablets, selecting pure water as the medium, maintaining the temperature at 37±1°C, detecting the phosphorescence lifetime and afterglow image of each tablet, and evaluating the disintegration time of the tablets.

[0010] As a preferred solution: the performance index of the tablets evaluated in step S4 includes the tablet mixing uniformity detection and evaluation: the tablets are irradiated with ultraviolet light, the afterglow image of the tablets is compared with the unevenly mixed drugs, the afterglow image is analyzed for grayscale value and the relative standard deviation of the grayscale value is calculated to evaluate the tablet mixing uniformity.

[0011] As a preferred solution: the performance index of the tablets evaluated in step S4 includes the detection and evaluation of the addition ratio of the auxiliary materials: the tablets are irradiated with ultraviolet light, and the addition ratio of the auxiliary materials is evaluated based on the display of the afterglow image of the tablets.

[0012] As a preferred solution: the performance index of the tablets evaluated in step S4 includes the hardness test and evaluation of the tablets: the phosphorescence lifetime and afterglow image of maltodextrin tablets of different hardness are detected and gray value analysis is performed to evaluate the hardness of the tablets.

[0013] As a preferred embodiment: the tablet comprises 20%-40% maltodextrin and 60%-80% povidone K30.

[0014] As a preferred embodiment: the tablet comprises 20%-80% maltodextrin and 20%-80% andrographolide powder.

[0015] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that: (1) The nondestructive testing method provided by the present invention can nondestructively test the characteristics of tablet hardness, humidity, disintegration time, and content uniformity.

[0016] (2) The nondestructive testing method provided by the present invention can determine whether the tablets are damp and deteriorated during transportation and storage, and has wide application value.

[0017] (3) The nondestructive testing method provided by the present invention is green, environmentally friendly, safe, generates no pharmaceutical waste, and has economic value.

[0018] (4) The raw material used in the present invention is maltodextrin, which has low sweetness, stable properties, and is often used as a pharmaceutical excipient. In addition, maltodextrins with different glucose equivalents have afterglow effects of different intensities and have potential application value.

[0019] In order to more clearly illustrate the structural features and effects of the present invention, it is described in detail below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The afterglow image of MCC PH101 under 254nm and 365nm ultraviolet light of the present invention; Figure 2 The afterglow images of MCC PH102, HPMC and HPC under 254nm and 365nm UV lamps of the present invention; Figure 3 The afterglow images of HPMCAC, SS and CMS under 254nm and 365nm ultraviolet lamps of the present invention are shown; Figure 4 The afterglow images of PVP K30 and LA under 254nm and 365nm UV lamps of the present invention; Figure 5 It is the afterglow image of MD under 254nm and 365nm ultraviolet lamp of the present invention; Figure 6 The afterglow images of the 70N and 100N hardness MD tablets of the present invention; Figure 7 Afterglow images of 130N and 160N hardness MD tablets of the present invention; Figure 8 Fitting the phosphorescence lifetime curve for the hardness 70N-MD tablet of the present invention; Fig. 9 Fitting the phosphorescence lifetime curve for the hardness 100N-MD tablet of the present invention; Fig.10 Fitting the phosphorescence lifetime curve for the hardness 130N-MD tablet of the present invention; Fig.11 Fitting the phosphorescence lifetime curve for the hardness 160N-MD tablet of the present invention; Fig.12 The moisture absorption of the MD tablets under different humidity conditions of the present invention; Fig.13 This is the afterglow image of the MD tablet stored in saturated K2SO4 and KI solution for 6 hours after being irradiated by 254nm ultraviolet light of the present invention; Fig.14 This is the afterglow image of the MD tablet stored in a saturated K2CO3, LiCl solution for 6 hours after being irradiated by a 254nm ultraviolet lamp according to the present invention; Fig.15 The relationship between the average gray value and the number of afterglow frames of the MD tablets under different humidity conditions of the present invention; Fig.16 The relationship between the initial gray value and the afterglow frame number of the MD tablet under different humidity conditions of the present invention; Fig.17The environmental conditions of the present invention are 25°C, saturated K2SO4, 6h, and the MD tablet is fitted with the phosphorescence lifetime curve; Fig.18 The environmental conditions of the present invention are 25°C, saturated KI, 6h, and the MD tablet is fitted with the phosphorescence lifetime curve; Fig.19 The environmental conditions of the present invention are 25°C, saturated K2CO3, 6h, and the MD tablet is fitted with the phosphorescence lifetime curve; Fig. 20 The environmental conditions of the present invention are 25°C, saturated LiCl, 6h, and the MD tablet is fitted with the phosphorescence lifetime curve; Fig.21 The relationship between the hardness and disintegration time of the MD tablet of the present invention; Fig. 22 The afterglow images of MD-AH tablets of different proportions according to the present invention; Fig.23 Afterglow images of MD-PVP tablets of different proportions according to the present invention; Fig.24 These are afterglow images of the PVP-MD 7:3 tablets and mixed uneven tablets of the present invention. DETAILED DESCRIPTION

[0021] The present invention Figure 1 As shown in FIG24 , a nondestructive testing method based on maltodextrin tablets comprises the following steps: S1. Preparing tablets: preparing a plurality of tablets containing maltodextrin of different hardness, wherein the hardness of each tablet is uniform; Maltodextrin was pressed in single punch mode by a multifunctional tablet press (manufacturer: ERWEKA, Germany, model: TR-D8), and the instrument parameters were adjusted to make tablets of different hardness (70N, 100N, 130N, 160N), with a tablet weight of 300 mg. The hardness of each tablet was tested by a tablet hardness tester to ensure that the tablet hardness was uniform under various parameter conditions. Before each sample was pressed, a blank piece of magnesium stearate was pressed to avoid sticking and lubrication.

[0022] S2. Test the phosphorescence lifetime of maltodextrin tablets: Use a transient / steady-state fluorescence spectrometer equipped with a xenon lamp and a microsecond flash lamp to fit the phosphorescence lifetime according to a multi-exponential function using the transient / steady-state fluorescence spectrometer software at an excitation wavelength of 240-260nm, and calculate the average phosphorescence lifetime (τ avg ); Phosphorescence lifetime is the decay curve of the monitored emission wavelength under light source excitation; S3. Detecting the afterglow image of the tablet containing maltodextrin: The afterglow image of the tablet is obtained by shooting. A 240-260 nm fixture UV lamp is fixed to the side of the tablet. After irradiation with the UV lamp for 5-15 seconds, the afterglow image is recorded. The afterglow image is analyzed frame by frame by video analysis software to capture the afterglow image of the tablet. The average gray value of the image is analyzed by "ImageJ" software to quantify the afterglow image. S4. Evaluate the performance indicators of the tablets based on the phosphorescence lifetime and afterglow image of the tablets.

[0023] The multi-exponential function used in fitting the phosphorescence lifetime in step S2 is: , and by the formula Calculate the average phosphorescence lifetime τ avg ; Where: R(t) represents the phosphorescence lifetime, t represents time, τ i Represents different types of phosphorescence lifetimes, including radiative transition lifetime τ1, non-radiative transition lifetime τ2, and other forms of lifetime τ3. Bi represents the percentage of different types of phosphorescence lifetimes.

[0024] The excitation wavelength in step S2 is 254 nm; in step S3, a 254 nm fixture UV lamp is fixed at a distance of 5 cm from the surface of the tablet, and after irradiation with the UV lamp for 10 seconds, an afterglow image is recorded for 5 seconds.

[0025] The performance indicators of the tablets evaluated in step S4 include humidity detection and evaluation of the tablets: maltodextrin tablets with a hardness of 100N are selected for a hygroscopicity experiment. The experiment is carried out according to the hygroscopicity guidelines in the general rules of Part IV of the 2020 edition of the "Chinese Pharmacopoeia". The biochemical incubator is set at 25°C, and the tablets are placed in a dryer with saturated salt. Four saturated salt solutions of LiCl, K2CO3, KI, and K2SO4 are prepared, and the relative humidity is set to 11%, 43%, 69%, and 94%, respectively. Environmental conditions for storage; after 6 hours, the tablets are taken out and the phosphorescence lifetime and afterglow image are detected to evaluate their humidity conditions.

[0026] The performance indicators of the tablets evaluated in step S4 include the disintegration time detection and evaluation of the tablets: according to the requirements for the disintegration time of tablets in the general rules of Part IV of the 2020 edition of the Chinese Pharmacopoeia; the method for determining the disintegration time is the hanging basket method, taking 6 tablets, using pure water as the medium, and maintaining the temperature at 37±1°C. Start the hanging basket to vibrate up and down, adjust the position of the hanging basket so that when it drops to the lowest point, the screen is 25 mm from the bottom of the beaker, and adjust the water level so that when the hanging basket rises to the highest point, the screen is 15 mm below the water surface; detect the phosphorescence lifetime and afterglow image of each tablet to evaluate the disintegration time of the tablet.

[0027] The performance index of the tablets evaluated in step S4 includes the tablet mixing uniformity detection and evaluation: 70% polyvidone (PVP K30) and 30% MD are mixed and compressed into tablets, the tablets are irradiated with ultraviolet light and compared with the unevenly mixed drugs, the afterglow image is analyzed for grayscale value and the relative standard deviation of the grayscale value is calculated to evaluate the tablet mixing uniformity.

[0028] The performance index of the tablets evaluated in step S4 includes the detection and evaluation of the addition ratio of the excipients: MD is mixed with the Chinese medicine powder Andrographis paniculata (AH) without afterglow in a ratio of 8:2 and with the excipient PVP in a ratio of 3:7 and then pressed into tablets; the tablets are irradiated with ultraviolet light, and the addition ratio of the excipients is evaluated based on the display of the afterglow image of the tablets.

[0029] The performance index of the tablets evaluated in step S4 includes the hardness test and evaluation of the tablets: the phosphorescence lifetime and afterglow image of maltodextrin tablets with different hardness are detected and gray value analysis is performed to evaluate the hardness of the tablets.

[0030] The tablets include 20%-40% maltodextrin and 60%-80% povidone K30 to evaluate the excipient specificity and tablet mixing uniformity.

[0031] The tablets included 20%-80% maltodextrin and 20%-80% andrographolide powder to evaluate excipient specificity.

[0032] Maltodextrin: It is a polysaccharide food raw material and is used as a filler for tablets. Since maltodextrin is a room temperature phosphorescent material with an afterglow effect, it is used as the main ingredient for non-destructive tablet testing.

[0033] Povidone K30: It is a non-functional excipient used as a tablet filler. It is used as a filling component for non-destructive tablet testing because it has no afterglow effect.

[0034] Andrographis paniculata powder: a spray-dried powder with brown color. Because it has no afterglow effect, it is used as a testing component for the specific addition ratio of MD excipients.

[0035] Example 1

[0036] Take powders of microcrystalline cellulose PH101 (MCC PH101), microcrystalline cellulose PH102 (MCC PH102), hydroxypropyl methylcellulose (HPMC), hydroxypropyl cellulose (HPC), hydroxypropyl methylcellulose acetate succinate (HPMCAC), soluble starch (SS), sodium carboxymethyl starch (CMS), povidone K30 (PVP K30), lactose (LA), and maltodextrin (MD), and fix them 5 cm away from the powder surface using a 365nm clamp UV lamp. Turn on the UV lamp and irradiate the surface of each powder for 10 seconds. After removing the light, record the afterglow image for 5 seconds.

[0037] Example 2

[0038] Take powders of microcrystalline cellulose PH101, microcrystalline cellulose PH102, hypromellose, hydroxypropyl cellulose, hypromellose acetate succinate, soluble starch, sodium carboxymethyl starch, povidone K30, lactose, and maltodextrin, and fix them 5 cm away from the powder surface using a 254nm clamp UV lamp. Turn on the UV lamp and irradiate the surface of each powder for 10 seconds. After removing the light, record the afterglow image for 5 seconds.

[0039] Example 3

[0040] MD was mixed with the non-afterglow Chinese medicine powder Andrographis paniculata (AH) at a ratio of 0:10, 2:8, 4:6, 6:4, 8:2, and 10:0, and with the non-functional excipient PVP at a ratio of 0:10, 2:8, and 4:6, and then tableted. The tablets were irradiated with ultraviolet light, and the specificity of the excipients under various substances was evaluated based on the display of the afterglow image of the tablets.

[0041] Example 4

[0042] The excipients PVP and MD without afterglow effect were mixed in a mass ratio of 8:2 and then tableted. The uniformity of the mixed tablets was judged by observing the afterglow image.

[0043] Comparative Example 1 To further illustrate the beneficial effects of the present invention, firstly, various pharmaceutical excipient powders are irradiated with ultraviolet light to explore whether there is an afterglow effect. The afterglow shooting method of this experiment is consistent with that of Example 1, and the difference from Example 1 is that different pharmaceutical excipient powders are used and irradiated with a 365nm ultraviolet lamp.

[0044] Comparative Example 2 To further illustrate the beneficial effects of the present invention, firstly, various pharmaceutical excipient powders are irradiated with ultraviolet lamps of different wavelengths to explore the optimal ultraviolet wavelength for the afterglow effect. The wavelength used in this experiment and Example 2 is 254nm, and the afterglow shooting method is the same. The difference from Example 2 is that various pharmaceutical excipient powders are used.

[0045] Comparative Example 3 To further illustrate the beneficial results of the present invention, the PVP and MD contents used in this experiment are different from those in Example 3. The mixing uniformity is determined by observing the afterglow image of the tablets. The remaining steps are the same as those in Example 3.

[0046] Effect example Figure 1-Figure 5Table 1 below shows the results of Example 1 and Example 2. It can be seen that MCC PH101, MCC PH102, HPMCAC, SS, and CMS have a microsecond afterglow phenomenon at 254nm, while MD has a millisecond afterglow phenomenon at 254nm, and the other pharmaceutical excipients have no afterglow effect at 254nm. MCC PH101 has a microsecond afterglow phenomenon at 365nm, while the other pharmaceutical excipients have no afterglow effect at 365nm. The above results show that the afterglow effect of MD under 254nm ultraviolet light is the most obvious, so MD is selected as the material for afterglow visualization non-destructive testing.

[0047] The MD was pressed into tablets of different hardness by a multifunctional tablet press, and tested by a hardness tester. The afterglow images of the MD tablets of different hardness were tested. The results are as follows: Figure 6 , Figure 7 shown.

[0048] Table 1: Afterglow duration of various drug excipients

[0049] In Table 1, microseconds and milliseconds indicate the length of the afterglow effect of each sample, and the “-” sign indicates no afterglow effect.

[0050] The afterglow image results of maltodextrin tablets at different hardness levels show that the brightness of the afterglow images of each tablet is close to the afterglow duration, and cannot be directly judged by the naked eye.

[0051] In this experiment, the transient / steady-state phosphorescence spectrometer was used to measure the phosphorescence lifetime of each tablet. The phosphorescence lifetime results, multi-exponential function fitting phosphorescence lifetime and average phosphorescence lifetime (τ avg ) The result is as follows Figures 8 to 11 And as shown in Table 2.

[0052] Table 2: Phosphorescence lifetime fitting curves of MD tablets with different hardness

[0053] Phosphorescence lifetime calculation formula: ; The average phosphorescence lifetime calculation formula is: ; The results in Table 2 show that the average phosphorescence lifetimes of maltodextrin tablets with hardness of 70N, 100N, 130N, and 160N are 65.1747ms, 67.1192ms, 67.8409ms, and 67.9765ms, respectively. The average phosphorescence lifetime is related to the hardness of the tablets and increases with the increase of the tablet hardness. Therefore, the hardness of the tablets can be detected by measuring the average phosphorescence lifetime of the tablets.

[0054] The hygroscopicity test was conducted on maltodextrin tablets with a hardness of 100N. Four environmental conditions were set at relative humidity of 11%, 43%, 69%, and 94%, respectively. The saturated salt solutions were K2SO4, KI, K2CO3, and LiCl, respectively. The hygroscopicity of the tablets was measured every 1 hour. Fig.12 shown.

[0055] Depend on Fig.12 It can be seen that the saturated potassium sulfate solution has the highest relative humidity and the strongest hygroscopicity, with a moisture absorption rate of 9.6% in 6 hours; the moisture absorption rates of saturated potassium iodide solution and saturated potassium carbonate solution in 6 hours are 3.93% and 1.69% respectively; and the saturated lithium chloride solution has the lowest relative humidity. The tablets lose weight under low relative humidity, with a weight loss rate of 0.43%.

[0056] In this experiment, the tablets were taken out after 6 hours of moisture absorption and the afterglow images of the tablets were detected. The experimental results are as follows Fig.13 , Fig.14 shown.

[0057] Depend on Fig.13 , Fig.14 It can be seen that the tablets stored in saturated potassium sulfate solution have too high moisture absorption rate and the afterglow effect is significantly weaker than other tablets. However, the brightness and duration of the afterglow are difficult to quantify with the naked eye. Therefore, this experiment proposes a new method to analyze the afterglow image of the tablet. The shot afterglow video is imported into the video editing software for processing, and the afterglow image is exported frame by frame, and the average grayscale value of each frame of the afterglow image is analyzed. The average grayscale value can quantify the brightness of the afterglow image to evaluate the strength of the afterglow image. Use Image software to analyze each frame of the afterglow image. When the afterglow image cannot be observed, the number of afterglow frames and the average grayscale value are measured. Therefore, the number of afterglow frames is used to evaluate the length of the afterglow time. The results of the average grayscale value, initial grayscale value and number of afterglow frames are shown as follows. Fig.15 , Fig.16 shown.

[0058] Depend on Fig.15 , Fig.16 It can be seen that the saturated K2SO4 solution has the highest relative humidity and the weakest afterglow effect, with an initial grayscale value of 0.192, and only about 7 frames of afterglow images are captured; the saturated KI and K2CO3 solutions have the second highest relative humidity, with initial grayscale values ​​of 0.335 and 0.381, respectively, and 15 and 23 frames of afterglow images appear; the saturated LiCl solution has the lowest relative humidity and the strongest afterglow effect, with an initial grayscale value of 0.520, and 23 frames of afterglow images.

[0059] The experiment was verified by testing the phosphorescence lifetime of MD tablets under various humidity conditions. The experimental results are shown in Table 3. Figure 17-Figure 20 shown.

[0060] Table 3: Phosphorescence lifetime fitting curves of MD tablets in different saturated salt solutions

[0061] Depend on Figure 17-Figure 20 Table 3 shows the verification results of the phosphorescence lifetime of tablets. The average phosphorescence lifetimes of tablets stored in saturated K2SO4, KI, K2CO3, and LiCl solutions are 66.4049ms, 78.0086ms, 84.7998ms, and 86.1494ms, respectively. The phosphorescence lifetime decreases with the increase of tablet humidity. The higher the humidity, the shorter the phosphorescence lifetime and the weaker the afterglow effect, which is consistent with the results of the above analysis using grayscale value and afterglow frame number. Therefore, the moisture absorption of tablets can be judged by the phosphorescence lifetime.

[0062] This experiment measured the disintegration time of the tablets. The results are as follows: Fig.21 shown.

[0063] Depend on Fig.21 It can be seen that the disintegration time of MD tablets with hardness of 70N, 100N, 130N, and 160N are 569±6s, 579±6s, 582±10s, and 606±9s, respectively. The trend of disintegration time is consistent with the tablet hardness. The greater the hardness, the longer the disintegration time. Therefore, the disintegration time of tablets can be evaluated by measuring the phosphorescence lifetime and afterglow effect of tablets.

[0064] Compared with Example 3, this experiment prepared tablets with MD-AH ratios of 0:10, 2:8, 4:6, 6:4, 8:2, and 10:0, and tablets with MD-PVP ratios of 0:10, 2:8, 3:7, 4:6, and 10:0. After irradiation with ultraviolet light, the afterglow images of the tablets were observed. The results are as follows: Fig. 22 , Fig.23 shown.

[0065] Depend on Fig. 22 , Fig.23 The experiment first proved that when the ratio of MD-AH and MD-PVP was 0:10, pure AH and PVP had no afterglow effect. When the ratio of MD-AH was 8:2, a weak but complete tablet outline could be observed in the afterglow image; when the ratio of MD-PVP was 2:8, only part of the tablet outline could be observed in the afterglow image of the tablet, not the complete tablet. When the ratio of MD-PVP was 3:7, the afterglow image of the tablet had a clear outline. The experimental results show that different Chinese medicines and excipients have different sensitivities to MD. The mixing ratio of each sample and MD determines the excipient specificity of the sample. The specific ratio of MD-AH is 8:2 and the specific ratio of MD-PVP is 3:7.

[0066] The experiment selected non-functional excipient PVP K30 without afterglow effect and MD specificity in a ratio of 7:3 and then pressed into tablets for content uniformity determination and compared with tablets with uneven mixing. The initial gray value, standard deviation, relative standard deviation of the tablets and the afterglow image results are shown in the figure. Fig.24 , as shown in Table 4.

[0067] Table 4: Initial gray value, standard deviation and relative standard deviation of PVP-MD-7:3 tablets

[0068] The experiment indicates the uniformity of tablet mixing by analyzing the initial grayscale value, standard deviation and relative standard deviation of the tablet afterglow image. The size of the initial grayscale value indicates the intensity of the afterglow image. The smaller the relative standard deviation, the more uniform the mixing. As shown in Table 4, the initial grayscale values ​​of the tablets with a PVP-MD ratio of 7:3 are 20.402, 19.964, and 19.131, and the relative standard deviations are 15.00%, 20.38%, and 15.28%, respectively. The results show that the order of mixing uniformity of the three tablets is: (1) > (3) > (2). Due to the uneven distribution of MD, the unevenly mixed tablets have an afterglow effect. The initial grayscale values ​​are 29.875 and 36.851, and the relative standard deviations are 88.87% and 36.70%, respectively, which are much larger than the relative standard deviations of other grayscale values. The order of mixing uniformity is: (5) > (4). Fig.24 It can be seen that the experiment can directly observe the integrity of the tablets through the afterglow image. The uniformly mixed tablets have an easily observable tablet outline, while the unevenly mixed tablets are incomplete tablets. The mixing uniformity of the tablets can be evaluated by the relative standard deviation of the gray value of the afterglow image.

[0069] The design emphasis of the present invention is: (1) The nondestructive testing method provided by the present invention can nondestructively test the characteristics of tablet hardness, humidity, disintegration time, and content uniformity.

[0070] (2) The nondestructive testing method provided by the present invention can determine whether the tablets are damp and deteriorated during transportation and storage, and has wide application value.

[0071] (3) The nondestructive testing method provided by the present invention is green, environmentally friendly, safe, generates no pharmaceutical waste, and has economic value.

[0072] (4) The raw material used in the present invention is maltodextrin, which has low sweetness, stable properties, and is often used as a pharmaceutical excipient. In addition, maltodextrins with different glucose equivalents have afterglow effects of different intensities and have potential application value.

[0073] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A nondestructive testing method based on maltodextrin tablets, characterized in that: The steps include: S1. Preparing tablets: preparing a plurality of tablets containing maltodextrin of different hardness, wherein the hardness of each tablet is uniform; S2. Test the phosphorescence lifetime of maltodextrin tablets: Use a transient / steady-state fluorescence spectrometer equipped with a xenon lamp and a microsecond flash lamp to fit the phosphorescence lifetime according to a multi-exponential function using the transient / steady-state fluorescence spectrometer software at an excitation wavelength of 240-260nm, and calculate the average phosphorescence lifetime τ based on the phosphorescence lifetime avg ; Phosphorescence lifetime is the decay curve of the monitored emission wavelength under light source excitation; S3. Detecting the afterglow image of the tablet containing maltodextrin: The afterglow image of the tablet is obtained by shooting. A 240-260nm fixture UV lamp is fixed to the side of the tablet. After irradiation with the UV lamp for 5-15 seconds, the afterglow image is recorded. The afterglow image is analyzed frame by frame by video analysis software to capture the afterglow image of the tablet. The average gray value of the image is analyzed by "ImageJ" software to quantify the afterglow image. S4. Evaluate the performance indicators of the tablets based on the phosphorescence lifetime and afterglow image of the tablets.

2. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The multi-exponential function used in step S2 to fit the phosphorescence lifetime is: , and by the formula Calculate the average phosphorescence lifetime τ avg ; Where: R(t) represents the phosphorescence lifetime, t represents time, τ i Represents different types of phosphorescence lifetimes, including radiative transition lifetime τ1, non-radiative transition lifetime τ2, and other forms of lifetime τ3. Bi represents the percentage of different types of phosphorescence lifetimes.

3. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The excitation wavelength in step S2 is 254 nm; in step S3, a 254 nm fixture UV lamp is fixed at a distance of 5 cm from the surface of the tablet, and after irradiation with the UV lamp for 10 seconds, an afterglow image is recorded for 5 seconds.

4. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The performance index of the tablets evaluated in step S4 includes humidity detection and evaluation of the tablets: maltodextrin tablets with a hardness of 100N are selected for a hygroscopicity experiment, the biochemical incubator is set at 25°C, the tablets are placed in a dryer containing saturated salt, four saturated salt solutions of LiCl, K2CO3, KI, and K2SO4 are prepared, and the relative humidity is set to 11%, 43%, 69%, and 94% respectively for storage; after 6 hours, the tablets are taken out and the phosphorescence lifetime and afterglow image are detected to evaluate their humidity conditions.

5. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The performance index of the tablets evaluated in step S4 includes the disintegration time detection and evaluation of the tablets: the disintegration time is determined by the hanging basket method, taking the tablets, selecting pure water as the medium, maintaining the temperature at 37±1°C, detecting the phosphorescence lifetime and afterglow image of each tablet, and evaluating the disintegration time of the tablets.

6. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The performance index of the tablets evaluated in step S4 includes the detection and evaluation of the tablets' mixing uniformity: the tablets are irradiated with ultraviolet light, and the brightness and distribution of the tablets' afterglow images are compared with those of unevenly mixed drugs, and the afterglow images are analyzed for grayscale values ​​and the relative standard deviation of the grayscale values ​​is calculated to evaluate the tablets' mixing uniformity.

7. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The performance index of the tablets evaluated in step S4 includes the detection and evaluation of the addition ratio of the auxiliary materials: the tablets are irradiated with ultraviolet light, and the addition ratio of the auxiliary materials is evaluated based on the display of the afterglow image of the tablets.

8. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The performance index of the tablets evaluated in step S4 includes the hardness test and evaluation of the tablets: the phosphorescence lifetime and afterglow image of maltodextrin tablets with different hardness are detected and gray value analysis is performed to evaluate the hardness of the tablets.

9. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The tablet comprises 20%-40% maltodextrin and 60%-80% povidone K30.

10. A nondestructive testing method based on maltodextrin tablets according to claim 1, characterized in that: The tablet comprises 20%-80% maltodextrin and 20%-80% andrographolide powder.

Citation Information

Patent Citations

  • High-flux near-infrared sensitive fast non-destructive analysis for impurities and tensile strength of tablets

    CN103792205A

  • Polysaccharide long-afterglow material and application thereof

    CN113621262A

  • Full-color long-afterglow composite material based on graft polymer PVA-g-PAM as well as preparation method and application of full-color long-afterglow composite material

    CN118126484A

  • Long-life room-temperature phosphorescent film and ultralow-temperature visual detection method thereof

    CN118580452A

  • Circular polarization room-temperature phosphorescent polymer film with adjustable afterglow color as well as preparation method and application of circular polarization room-temperature phosphorescent polymer film

    CN119242295A